PENGARUH BEBAN KERJA DAN TEAMWORK TERHADAP KEPUASAN KERJA DAN PRODUKTIVITAS KERJA KARYAWAN PADA PT PERTAMINA HULU ROKAN ZONA XXX - Fadhil Rifqi Pratama; Susi Hendriani; Machasin Machasin (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
Oil and gas industry is one of the industry that demand human resources with high competency due to work risk and one of the Indonesia’s government backbone in generating revenue for the country. PT Pertamina Hulu Rokan Zona XXX is one of PT Pertamina (Persero) business subsidiary focusing on exploration and exploitation of oil in gas within Sumatra island. PT Pertamina Hulu Rokan Zona XXX is responsible in managing oil and gas block from Jambi Province to Nanggroe Aceh Darussalam Province, so that managing human resources is crucial to help the company reach its own target. To reach its target, employee work productivity plays an important role. Variable used to measure employee work productivity is workload, teamwork and job satisfaction. This research aims to analyze the interaction between every variables in employee work productivity on PT Pertamina Hulu Rokan Zona XXX. The result of this study indicate that workload, teamwork and job satisfaction have a significant effect on employee work productivity, where workload giving a negative effect empoloyee work productivity, teamwork and job satisfaction giving positive effect on employee work productivity. Conclusion of this research is that workload giving negative effect and significant on job satisfaction as well as employee work productivity due to high workload with insufficient appreciation from the company causing the job satisfaction decreases which imply on the reduction of employee work productivity. Meanwhile, teamwork giving positive effect and significant on job satisfaction, since increase in teamwork attitude within colleagues will raise employee work productivity on PT Pertamina Hulu Rokan Zona XXX.